2000
DOI: 10.1046/j.1365-2133.2000.03351.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of pancreatic type I secreted phospholipase A2 in human epidermis and its determination by tape stripping

Abstract: Phospholipases A2 (PLA2) catalyse the release of fatty acids from the sn-2 position of phospholipids and have been suggested to play a key part in permeability barrier homeostasis. Using a sensitive and versatile fluorometric method, significant PLA2 activity has been detected in both human skin homogenates and tape strippings of stratum corneum. Based on various properties (resistance to heat and sulphuric acid treatment, neutral optimal pH, absolute requirement for millimolar calcium concentrations, inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…It has been reported that type I PLA2, the pancreatic form, is essentially located at the interface between the stratum granulosum and the stra-tum corneum [9]. This location coincides with that of the lysis of phospholipids into free fatty acids, i.e.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…It has been reported that type I PLA2, the pancreatic form, is essentially located at the interface between the stratum granulosum and the stra-tum corneum [9]. This location coincides with that of the lysis of phospholipids into free fatty acids, i.e.…”
Section: Discussionmentioning
confidence: 88%
“…Concerning phospholipase A2-like activity (table 2), it has been shown as resulting from the presence of both type I PLA2 [9] and type II PLA2 [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies on this protein are interesting because the presence of type I PLA 2 proteins was demonstrated in various tissues, including kidney, small intestine, spleen, lung, and stomach (55). A pancreatic type I PLA 2 was recently identified in the human epidermis (56). Moreover, the presence of a PLA 2 , which is revealed by immunostaining with antibodies raised against the porcine pancreatic enzyme, was detected in the acrosomal region of human spermatozoa (57).…”
Section: X-ray Diffraction Datamentioning
confidence: 99%
“…Whereas epidermis also expresses two other sPLA 2 isoforms [42,43,48,49], group II and group X sPLA 2 , neither of these sPLA 2 are expressed in the outer epidermis under basal conditions. Moreover, based upon its inhibitor profile, its sensitivity to dithiothreitol, its pH optimum (= 7), its resistance to both heat and sulfuric acid, its Ca 2+ requirement and its immunohistochemical localization, much if not all of the sPLA 2 activity in the SC comprises the group 1 (pancreatic-type) sPLA 2 [44,45]. Like its lipid substrates, sPLA 2 activity localizes to lamellar bodies and within the SC interstices [34,37,[50][51][52][53], while in contrast, other potential epidermal sources of FFA (e.g.…”
Section: Phospholipid-to-ffa Pathwaymentioning
confidence: 99%